Erosion resistance of coatings exposed to microimpacts - Воеводин, Виктор Николаевич; Картмазов, Геннадий Николаевич; Маринин, Владимир Григорьевич (Eastern-European Journal of Enterprise Technologies, 2014)
We have studied erosion of nichrome, titanium, titanium nitride, chrome, and chrome carbide coatings impacted by cavitation. The coatings are obtained by applying plasmatron, detonation, vacuum and arc as well as atomic and ionic sedimentation methods. Ultra-sound cavitation was created in water; the fluctuation amplitude of the emitting vibrator surface was equal to 30±2 µm with the frequency of 20±2 kHz. The erosion was assessed by the gravimetric method with the precision of up to 0.015 mg. The kinetic curves on the dependence of the eroded mass quantity upon cavitation time have determined the velocity of coating deterioration as well as coating durability. The research has proved that coatings precipitated by plasmatron and detonation methods have low resistance to erosion and deteriorate 3-5 times quicker than steel of the 15H11MF variety because such coatings have a layered structure resulting from a discreet supply of material to the specimen and formation of intermediate brittle layers between the supplies. The result is low resistance of the interlayer boundaries and the coating as a whole. Vacuum and arc titanium, titanium nitride as well as atomic and ionic chrome, carbon-doped coatings have a certain mass loss resistance that exceeds steel durability up to 5-8 times. The research has proved that durability of atomic and ionic coatings depends on their microhardness, whereas coatings with microhardness of 8-10 GPa have an optimal resistance to erosion.